Regulation of microglia phagocytosis and potential involvement of exercise - Li, Congqin; Wang, Yong; Xing, Ying; Han, Jing; Zhang, Yuqian; Zhang, Anjing; Hu, Jian; Hua, Yan; Bai, Yulong (Frontiers in Cellular Neuroscience, 2022)
In the central nervous system, microglia are considered as the main cells responsible for phagocytosis, contributing to neural circuit refinement and homeostasis through synapse elimination during development. Microglial phagocytosis is also a crucial process in maintaining adult brain homeostasis and clearing potential toxic factors, which are recognized to be associated with neurodegenerative and neuroinflammatory disorders. Microglia can engulf cellular debris and harmful molecules such as amyloid-β plaques through the expression of specific receptors at their surface and activation of downstream signaling pathways. Furthermore, Physical exercise is an effective therapy for neurorehabilitation which has been shown to be closely related to neuroplasticity and microglia functions including proliferation, activation and phagocytosis. This review focuses on the central regulatory mechanisms related to microglia phagocytosis and the potential role of exercise training in this process.